Exploring the Domain of Emotional Intelligence in Organizations: Bibliometrics, Content Analyses, Framework Development, and Research Agenda - Dong, Baobao; Peng, Xing; Jiang, Na (Frontiers in Psychology, 2022)
Emotion is a kind of micro foundations that can affect human behaviors even in digital era. Emotional intelligence (EI) is an important psychological factor that affects the growth and development of organizations from the view of emotion. Based on the current literatures, a comprehensive review of EI can contribute to its theory development in organization research and facilitate EI research burgeoning. We visualized the landscape of EI by analyzing 1996 articles with CiteSpace in its concepts, dimensions and measurement. And we propose two specific mechanisms which clarify how individuals with high EI use emotional information to influence themselves and others respectively. Following this, we develop a theoretical framework of EI from the cross level of individual, team and organization. Finally, future directions and research agenda are addressed. This research contributes to the literature of EI and provide practical insight for practitioners.